Trop-2 plasticity is controlled by epithelial-to-mesenchymal transition - Remšík, Ján; Binó, Lucia; Kahounová, Zuzana; Kharaishvili, Gvantsa; Šimecková, Šárka; Fedr, Radek; Kucírková, Tereza; Lenárt, Sára; Muresan, Ximena Maria; Slabáková, Eva; Knopfová, Lucia; Bouchal, Jan; et al. (Carcinogenesis, 2018)
The cell surface glycoprotein Trop-2 is commonly overexpressed in carcinomas and represents an exceptional antigen for targeted therapy. Here, we provide evidence that surface Trop-2 expression is functionally connected with an epithelial phenotype in breast and prostate cell lines and in patient tumor samples. We further show that Trop-2 expression is suppressed epigenetically or through the action of epithelial-to-mesenchymal transition transcription factors and that deregulation of Trop-2 expression is linked with cancer progression and poor patient prognosis. Moreover, our data suggest that the cancer plasticity-driven intratumoral heterogeneity in Trop-2 expression may significantly contribute to response and resistance to therapies targeting Trop-2-expressing cells.
Keywords: DNA Methylation; Cell Adhesion Molecules; Male; epitelové buňky; progrese nemoci; Cell Line, Tumor; metylace DNA; Epithelial-Mesenchymal Transition; Cadherins; Antigens, CD; Epithelial Cells; CD antigeny; Xenograft Model Antitumor Assays; molekuly buněčné adheze; antigeny nádorové; myši inbrední BALB C; Prostatic Neoplasms; nádory prsu; mužské pohlaví; Disease Progression; Mice, Inbred BALB C; xenogenní modely - testy protinádorové aktivity; Animals; lidé; Carcinoma; ženské pohlaví; Breast Neoplasms; Humans; zvířata; nádory prostaty; kadheriny; karcinom; Antigens, Neoplasm; myši; nádorové buněčné linie; Mice; Female; epitelo-mezenchymální tranzice